Passengers Opinion Regarding Digitalization Process of Indian Railways - Kaur , Navjot; Sharma , Meena (Gyan Management Journal, 2018)
Indian Railways is one of the oldest and cheapest transport systems in the world. It plays a pivotal role in the growth of economy because of its usage in India (number of passengers and employment). "It is the world's eighth largest single employer with 13,26,437 employees in India. It has multi gauge system with total route kilometrage 66002.36 km of which 22197.01 km is electrified". (Source: Annual Statistical Statementoflndian Railways 2015-16)At one point of time Indian Railways was facing the challenge of bankruptcy. But with the advent of technology in railways, 2004 was the turning point in the history of Indian Railways. Electronic transformation in Indian Railways not only created ease in availing railway services but also saved it from financial crises. In 2004, Ministry of Indian Railways took a major decision to digitalize the Indian Railways. The objective of digitalization of Indian Railways was to provide access and affordable mode of transport for every person oflndia. Digitalization oflndian Railways is not only expected to save the time and money of customers but also reduce the cost of infrastructure such as building, furniture, electricity etc for Indian Railways. It transforms the life of customer's right from ticket reservation to online food services.
Keywords: Indian Railways; passengers; technology; transport; Digitalization